Improving Market Performance in The Digital Era: The Role of Collaboration, Marketing Innovation - Sholihah, Zilfatus; Pujianto, Wahyu; Boyaz, Jeziano Rizkita; Afifatus Sholikhah (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
This study analyzes the influence of collaboration, marketing innovation, and organizational creativity on market performance in the digital era, with entrepreneurial innovation as a moderator variable. This research was conducted in Sidoarjo and Surabaya, using quantitative methods and SmartPLS to test research hypotheses. Data collection was carried out by distributing questionnaires designed by researchers. The results of this study show that collaboration marketing innovation does not influence market performance where collaboration has a gap in market performance. In contrast, organizational creativity has a significant influence on market performance, where organizational creativity is considered to be able to develop a company's innovation.